Serotonin transporter gene polymorphism implicates reduced orbito-frontal cortex in obsessive-compulsive disorder - Atmaca, Murad; Onalan, Ebru; Yildirim, Hanefi; Yuce, Huseyin; Koc, Mustafa; Korkmaz, Sevda; Mermi, Osman (Pergamon-Elsevier Science Ltd, 2011)
Although a number of magnetic resonance imaging (MRI) and genetic studies have been performed on obsessive-compulsive disorder (OCD), only limited studies in which genetic and neuroanatomical variables are evaluated concurrently have been performed. Therefore, the aim of our present study is (to understand) better understanding how genetic variation in the promoter region of the 5-HTT gene (5-HTTLPR) is associated with key brain structures in OCD, orbito-frontal cortex (OFC), thalamus and anterior cingulate. 5-HTT genotypes (SS, SL, LL) were determined for 40 patients with OCD and the same number of healthy controls. MRI-derived volumes of the OFC, thalamus, and anterior cingulate were determined by reliable tracing techniques. Volumetric measurements were made with T1-weighted coronal MRI images, with 1.5-mm-thick slices, at 1.5 T, and were done blindly. In comparison with controls, OCD patients demonstrated volumes reduction in OFC, increased volumes of thalamus and total white matter volumes, but no difference in total brain volume, total gray matter volumes and anterior cingulate volumes. No significant difference was observed in allelic frequencies between the patients and controls. The stronger effects of 5-HTT polymorphism on brain morphology in OCD than those in controls were determined in the both OFC and thalamus. On the other hand, for the OCD patients, ANCOVA revealed a significant main effect of genotype for both the OFC and thalamus and a significant genotype-by-side interaction for the OFC, demonstrating that the short variants had a smaller right OFC than the long variants. In conclusion, we found a significant genotype-diagnosis interaction effects on key brain structures, with a stronger effects of 5-HTT polymorphism in OFC and thalamus of OCD patients, whereas no morphological changes related to the polymorphism were found in normal individuals. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: 5-HTT; MRI; OCD; OFC; Thalamus